Extraction method for fossil pollen grains using a cell sorter suitable for routine 14C dating. (15th November 2021) - Yamada, Keitaro; Omori, Takayuki; Kitaba, Ikuko; Hori, Tatsuo; Nakagawa, Takeshi
Abstract: Fossil pollen grains have long been recognised as potentially ideal materials for radiocarbon dating. In recent years, the development of cell sorter technology has made it possible to date fossil pollen grains. Although various approaches have been proposed, none of them is being practiced routinely because of the difficulty in stably and efficiently extracting small fossil grains at high enough purity from a variety of sediments. Here we show a new method which allows routine extraction and reliable radiocarbon dating of fossil pollen grains, even from organic-rich sediments. The improved physicochemical pre-treatment enables efficient enrichment from large volume of organic-rich sediments without the use of an oxidant. We also propose new sorting criteria consisting of multi-step 'gates', each of which is based upon fluorescence characteristics and scattered light of the particles. The sorting method, combined with the improved physicochemical pre-treatments, makes it possible to separate small fossil pollen grains from impurities such as green algae, micro charcoal, spores and plant fragments using a cell sorter. In particular, relatively small fossil pollen grains, with which previously proposed methods tended to suffer, could be extracted from organic-rich lacustrine sediments and organic peats in a remarkably high purity and velocity using our method. Radiocarbon ages subsequently measured on fossil pollen concentrates prepared by our method show very good agreement with those of terrestrial leaf fossils extracted from the same sediments of Lake Suigetsu, which directly record atmospheric 14 C. The extraction method provides a new opportunity to routinely determine ages of sediments that do not contain contemporaneous macrofossil remains, and allow us to increase the precision of age models by strategically selecting horizons for dating prior to incorporation into Bayesian chronological modelling. Highlights: A new method using a cell sorter enables fast and high-purity pollen extraction. 14 C ages of fossil pollen grains show good agreement with those of leaf fossils. The new method is demonstrated to be ready for routine application.